2005
DOI: 10.1007/s00213-004-2099-9
|View full text |Cite
|
Sign up to set email alerts
|

Metabotropic glutamate 2 receptor potentiators: receptor modulation, frequency-dependent synaptic activity, and efficacy in preclinical anxiety and psychosis model(s)

Abstract: Taken together, the data indicate mGlu2 receptor potentiators have a unique use-dependent effect on presynaptic glutamate release, and show efficacy in several mGlu2/3-sensitive animal models of psychiatric disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
122
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(131 citation statements)
references
References 51 publications
8
122
1
Order By: Relevance
“…In addition, the mutations did not prevent the 7TM domain from activating G proteins. The positive allosteric modulator (PAM), LY487379, which binds to the 7TM (26,27), activated all mutants except the C500A mutant (Fig. 1C); this is in agreement with our previous reports that mGluR PAMs become full agonists when the 7TM is disconnected from the VFT (24,28).…”
Section: Resultssupporting
confidence: 92%
“…In addition, the mutations did not prevent the 7TM domain from activating G proteins. The positive allosteric modulator (PAM), LY487379, which binds to the 7TM (26,27), activated all mutants except the C500A mutant (Fig. 1C); this is in agreement with our previous reports that mGluR PAMs become full agonists when the 7TM is disconnected from the VFT (24,28).…”
Section: Resultssupporting
confidence: 92%
“…2B) from adult (2-to 3-mo-old) P and NP rats. Whereas application of 200 nM LY379268 produced a 40-60% decrease below baseline levels in both regions in NP rats, consistent with the synaptic depression previously observed in DG and striatum of Sprague-Dawley rats (20,21), we observed less than 10% depression in P rats, consistent with uncompensated loss of mGluR2 function.…”
Section: Significancesupporting
confidence: 91%
“…These receptors are primarily located presynaptically and function as auto-receptors. mGluR2 is thought to be the receptor primarily responsible (20) for the group II mGluR-mediated presynaptic depression of glutamatergic neurons projecting onto striatum (21). Using field potential recordings, we examined effects of the group II mGluR agonist LY379268 on the synaptically evoked field excitatory postsynaptic potential (fEPSP) or population spike (PS) in dentate gyrus (DG)/hippocampal ( Fig.…”
Section: Significancementioning
confidence: 99%
“…At present, eight subtypes of mGlus receptors have been identified, which can be subdivided into three groups (group I: mGlu1,5;group II: mGlu2,3;group III: mGlu4,6,7,8) based on their molecular structure, intracellular transduction pathway, and pharmacological profile (Conn and Pin 1997;Schoepp et al 1999). Group II mGlu ligands seem to be drugs with a particular promising therapeutic potential in psychiatric disorders, including anxiety and depression (Johnson et al 2005;Palucha and Pilc 2007). Group II mGlus are widely expressed in the rodent forebrain, although the distribution of mGlu2 is more restricted than that of mGlu3 (Ferraguti and Shigemoto 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Activation of mGlu2 and mGlu3 by LY354740 elicits inhibitory responses and has frequently been reported to have anxiolytic-like properties in various anxiety-related tests, such as stressinduced hyperthermia and the elevated plus maze in wildtype (WT) mice (Helton et al 1998;Linden et al 2004;Linden et al 2005a;Monn et al 1997;Spooren et al 2002;Johnson et al 2005;Galici et al 2006). Interestingly, recent studies involving mice lacking mGlu2 or mGlu3 receptors revealed that stimulation of both of these subtypes is necessary to observe anxiolytic-like efficacy of LY354740, since this effect was abolished in both knockout strains (Linden et al 2005b).…”
Section: Introductionmentioning
confidence: 99%